PENGARUH PEMBELAJARAN DARING (GOOGLE CLASSROOM) DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Rahmi Maiyunda Sari; Saleh Haji; Zamzaili Zamzaili (LPPM Universitas Bina Bangsa, 2023)
This research aims to determine the effect of online learning (Google Classroom) using a scientific approach based on ethnomathematics on the mathematical problem solving and communication abilities of class VIII students at SMPN 02 Bengkulu City. This research is quantitative research with a quasi-experimental method. The population in this study were class VIII students at SMPN 02 Bengkulu City, Even Semester, 2020/2021 Academic Year. The sample for this research was class VIII C students as an experimental class by implementing online learning (Google Classroom) using an ethnomathematics-based scientific approach to mathematical problem solving and communication skills and class VIII A students as a control class by applying conventional learning via WhatsApp. The results of this research show that the Ftable value = 3.99. The results of learning using online (Google Classroom) with conventional learning on problem solving abilities Fcount = 7.9. The results of the problem-solving abilities of students with high abilities and students with low abilities Fcount = 8.86, and the results of the interaction of learning factors and abilities on students' problem-solving abilities Fcount = 7.41. It can be concluded that Fcount > Ftable, then H0 is rejected, so there is an influence of online learning (Google Classroom) using a scientific approach based on ethnomathematics on the problem-solving abilities of class VIII students at SMPN 02 Bengkulu City